MAQSUD SHAIKHZODA'S SKILL IN USING SYNONYMS - Maxanova Feruza Mamarajabovna (Web of Journals Publishing, 2025)
In this article reflects on the linguistic features of synonyms Maqsud Shaikhzoda's skill in using synonyms. Some considerations have been expressed on the role of syntactic tools in the formation of the aesthetic influence of Maqsud Shaikhzoda's poems and on the linguistic aspects of synonyms found in his poems.
Keywords: Synonyms, linguopoetic properties, polesemantics, lexeme, lexical and contextual synonyms, context.